Implementation Of The Change Of The Chairman Of The Labuhan Batu Selatan Regional People's Representative Council - Zainuddin Zainuddin (International Journal Reglement & Society (IJRS), 2022)
The Provincial Government has a Governor, the Regency Regional Government has a Regent and Regency DPRD, and the City Regional Government has a Mayor and City DPRD. More specifically, Article 18 Paragraph (3) of the 1945 Constitution which states "Provincial, Regency and City Regional Governments shall have a Regional People's Representative Council whose members are elected through general elections". That is, in every Regional Government, Regency and City has a Government that is accompanied by the Regional People's Representative Council. The appointment of the chairman of the DPRD is based on the rules that have been set, namely based on the votes obtained and based on that it can be said that the appointment based on the procedure also has an opponent, namely the dismissal that is carried out based on the procedure. The purpose of this study was to find out the legal arrangements regarding the Regional People's Representative Council, to find out the legal basis for the replacement of the Chair of the South Labuhan Batu Regional People's Representative Council, and to find out the process of implementing the replacement of the Chair of the South Labuhan Batu Regional People's Representative Council. Regarding the legal arrangements regarding the Regional People's Representative Council, it is regulated in Article 18 Paragraph (1) of the 1945 Constitution and the provisions regarding Regional Heads and Deputy Regional Heads can be found in Law Number 23 of 2014 concerning Regional Government. As has been amended several times, most recently by Law Number 9 of 2015, Substitution of the Chairperson of the Labuhan Batu Selatan Regional People's Representative Council through the results of a meeting held in the meeting room of the Labuhan Batu Selatan Regional People's Representative Council and on the basis of a letter submitted by the Regional Leadership Council National Mandate Party and answered by the Central Executive Board of the National Mandate Party to approve the replacement of the Chairman of the Regional People's Representative Council of South Labuhan Batu with Letter Number: PAN/A/KU-SJ/100/VIII/2016 dated August 16, 2016 Regarding Approval of the Name of the Chairman of the DPRD Labusel Regency From the DPP PAN and even then addressed to the Chairman of the DPD PAN Labusel, the process of replacing the Chairman of the Regional House of Representatives for the South Labuhan Batu Region is carried out in accordance with the applicable laws and regulations